Identificación y localización de fallas en sistemas de distribución, utilizando medidores de calidad del servicio de energía eléctrica - César Hernández; Robín A. Peña; Víctor A. Gómez (Revista Científica, 2011)
This paper presents a new methodology for iden- tifying and locating faults in distribution systems of electric power, through the implementation of electronic meters that record the continuity of electric service. The implementation of the meters, to provide detection permanent or transient fault in non-homogeneous networks and providing in- formation of weaknesses in the power system and then to take corrective action with respect to the duration and frequency of breaks in the circuits lo- cal distribution systems. By means of this mechanism regulation of the sys- tems from the generation, marketing, distribution and operation of electricity. This raises a solution to mitigate the discontinuity of service and signifi- cant costs to produce electricity smainly to electricity users.